2020
DOI: 10.5267/j.ijdns.2020.2.002
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of technology transfer in Vietnam: An empirical analysis

Abstract: This paper examines the determinants of technology transfer through international trade in Vietnam by using provincial level data. The paper investigates the similarities and differences between the adoption of technology from OECD and non-OECD countries. The empirical finding shows that the skills of labor force and openness to trade are the most robust determinants of technology adoption at the provincial level. Furthermore, provinces with higher levels of R&D expenditure adopt more technology from OECD coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…There are few studies that have touched the issue. In a recent study, Hoang et al (2021) have briefly found that FDI has limited influence on local firms' technology and innovation by looking at only manufacturing firms in one city of Vietnam (Hanoi) or Nguyen and Le (2020) investigate the spillovers at provincial level. Doan (2018) briefly summarizes the experience of some European countries that have welcomed foreign firms in order to boost domestic R&D activity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are few studies that have touched the issue. In a recent study, Hoang et al (2021) have briefly found that FDI has limited influence on local firms' technology and innovation by looking at only manufacturing firms in one city of Vietnam (Hanoi) or Nguyen and Le (2020) investigate the spillovers at provincial level. Doan (2018) briefly summarizes the experience of some European countries that have welcomed foreign firms in order to boost domestic R&D activity.…”
Section: Literature Reviewmentioning
confidence: 99%